Navigating the Risk Terrain in Small Business Economics: Menavigasi Medan Risiko dalam Ekonomi Bisnis Kecil - Tursunov Mansur Bekpulatovich (Universitas Muhammadiyah Sidoarjo, 2024)
This article explores various methods for analyzing and assessing the risks faced by small businesses, emphasizing economic and financial indicators. Key areas of risk assessment include identification, analysis, and comparative evaluation of risks, each employing specific tools. The study highlights the importance of understanding operational risks, based on ISO 31000:2009 standards, and provides detailed methods for evaluating risks related to assets, solvency, and financial stability. It also discusses the implications of liquidity and solvency risks on business operations, offering a structured approach to mitigating these risks. Highlights: Identify Risks: Focus on assets, solvency, and liquidity risks. Operational Standards: Use ISO 31000:2009 to manage operational risks. Financial Analysis: Evaluate stability and solvency for business growth. Keywords: Risk Assessment, Small Businesses, Economic Indicators, Financial Stability, ISO 31000